Kanani Ku: capstone - Ku, Kanani, artist (Colorado State University. Libraries, 2024)
The artist's statement: As a potter, I create work that exemplifies the beauty of clay. By allowing my material to guide me as a maker, the clay pushes for new and exciting possibilities that might have gone unnoticed. Pottery is naturally beautiful and that formal tactility is why I enjoy this material so much. I work mainly on the wheel, using this wonderful tool to stretch and form the clay into a hollow volume, from there I push the boundaries of traditional set aesthetics by celebrating the unique imperfections of the me [the makers] hands through fingerprints and the evidence of human element through asymmetry. Through working the with the wheel as a tool and embrace the evidence of my hands I have found extreme satisfaction from clay.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery